The Effects of Anthropogenic Stressors on Reproduction and Recruitment of Corals and Reef Organisms - Richmond, Robert H.; Tisthammer, Kaho H.; Spies, Narrissa P. (Frontiers in Marine Science, 2018)
The persistence of populations of marine organisms depends on the success of the dual processes of reproduction and recruitment. The production of offspring alone is inconsequential unless larvae and propagules can recruit, which often entails a period of development and distribution in the water column and subsequent selection of appropriate habitats. For fish, this may mean drifting in currents before responding to particular habitat cues. For corals and other benthic invertebrates, larvae must undergo site selection, settlement and metamorphosis into the juvenile form, and survivorship is directly linked to site choice and environmental conditions. Both biotic and abiotic factors affect population replenishment success, and hence, anthropogenic influences such as pollution, sedimentation and climate change can negatively affect critical processes such as reproductive synchronization in spawning species, successful embryological development, appropriate site selection, settlement, metamorphosis and in the case of reef building corals, acquisition of the required zooxanthellae partner. Effective management practices are essential for ensuring the persistence of populations of coral reef organisms of economic, cultural and ecological value.